Resistance to the Insulin and Elevated Level of Androgen: A Major Cause of Polycystic Ovary Syndrome - Ding, Haigang; Zhang, Juan; Zhang, Feng; Zhang, Songou; Chen, Xiaozhen; Liang, Wenqing; Xie, Qiong (Frontiers in Endocrinology, 2021)
PCOS has a wide range of negative impacts on women's health and is one of the most frequent reproductive systemic endocrine disorders. PCOS has complex characteristics and symptom heterogeneity due to the several pathways that are involved in the infection and the absence of a common cause. A recent study has shown that the main etiology and endocrine aspects of PCOS are the increased level of the androgen, which is also known as "hyperandrogenemia (HA)” and secondly the “insulin resistance (IR)”. The major underlying cause of the polycystic ovary is these two IR and HA, by initiating the disease and its severity or duration. As a consequence, study on Pathogenesis is crucial to understand the effect of “HA” and “IR” on the pathophysiology of numerous symptoms linked to PCOS. A deep understanding of the pattern of the growth in PCOS for HA and IR can help ameliorate the condition, along with adjustments in nutrition and life, as well as the discovery of new medicinal products. However, further research is required in order to clarify the mutual role of IR and HA on PCOS development.